Komunikasi Dakwah Terapeutik Dikalangan Public Figure - Muhajir, Ahmad (TSAQOFAH, 2024)
Therapeutic dawah communication among public figures is an increasingly prominent phenomenon in the digital era. Public figures, including artists and celebrities, leverage their popularity and influence to convey religious and moral messages to a wide audience. This therapeutic dawah focuses not only on spreading religious teachings but also on providing emotional and psychological support to their followers. By utilizing social media platforms, public figures can reach millions of followers directly, creating personal and deep interactions. The essence of therapeutic dawah communication among public figures includes attention, role modeling, relevance, inclusiveness, and personalization. Public figures can capture the attention of many people and set themselves as positive examples. Their use of modern language and communication styles makes their dawah relevant and easily accepted by various groups, especially the younger generation. An inclusive approach and universal messages help reduce stigma and strengthen interfaith tolerance. Furthermore, personalizing dawah messages based on the public figure’s personal experiences makes the messages more authentic and inspiring. This study aims to analyze the effectiveness and impact of therapeutic dawah communication carried out by public figures. By employing case study methods, content analysis, and library research, this research will explore how public figures utilize digital platforms for dawah and the psychological impact on their followers. The results of this study are expected to provide new insights into modern dawah strategies and their contribution to the mental and spiritual health of the community.